Sublime encounters: Commodifying the experience of the geos. Issue 2 (19th December 2018) - Donovan, Amy
Abstract : This paper discusses the rise in volcano tourism in the last few decades, focusing on its impact in recent eruptive crises in Iceland. The paper uses evidence from ethnographic research and surveys to argue that two divergent economic narratives come into conflict around volcanoes: the problematisation of the earth as potentially risky, and the elevation of those risky behaviours as something worth commodifying. Icelandic civil protection ( Almannavarnir ) have increasingly become concerned about the behaviour of tourists around active volcanoes, particularly during eruptions. However, this is also a considerable opportunity for tour groups. During the 2014–2015 eruptions at Holuhraun, there was concern about high levels of gas that were being emitted, and so tourists were banned from the site. This led to clandestine efforts to get in by helicopter after dark. The felt need for these experiences can be traced back at least to the Enlightenment period, and denotes an example of affective commodification, as the sublime encounter between humans and raw energy of the earth is rendered valuable in monetary terms – and yet transcends commodification in a simple sense. Abstract : This paper discusses scientific and economic aspects of two recent Icelandic eruptions, focussing particularly on the tension between tourism, which commodifies the experience of the earth, and risk management, which limits it. e00067